Past, Present and Future: The Relationship Between Circular RNA and Immunity - Gu, Junjie; Su, Chongying; Huang, Fei; Zhao, Yuwei; Li, Jing (Frontiers in Immunology, 2022)
The immune system has evolved since the birth of humans. However, immune-related diseases have not yet been overcome due to the lack of expected indicators and targeting specificity of current medical technology, subjecting patients to very uncomfortable physical and mental experiences and high medical costs. Therefore, the requirements for treatments with higher specificity and indicative ability are raised. Fortunately, the discovery of and continuous research investigating circular RNAs (circRNAs) represent a promising method among numerous methods. Although circRNAs wear regarded as metabolic wastes when discovered, as a type of noncoding RNA (ncRNA) with a ring structure and wide distribution range in the human body, circRNAs shine brilliantly in medical research by virtue of their special nature and structure-determined functions, such as high stability, wide distribution, high detection sensitivity, acceptable reproducibility and individual differences. Based on research investigating the role of circRNAs in immunity, we systematically discuss the hotspots of the roles of circRNAs in immune-related diseases, including expression profile analyses, potential biomarker research, ncRNA axis/network construction, impacts on phenotypes, therapeutic target seeking, maintenance of nucleic acid stability and protein binding research. In addition, we summarize the current situation of and problems associated with circRNAs in immune research, highlight the applications and prospects of circRNAs in the treatment of immune-related diseases, and provide new insight into future directions and new strategies for laboratory research and clinical applications.